Comparison of quality of life between hemophilic children receiving prophylaxis and on demand therapy in Tehran - Khanali Mojen, Leila; Abed Saeedi, zhila; Eshghi, peiman; Farahani, hojat; Abdollah Gorgi, fatemeh; Habibpanah, behnaz; Tehrani Tarighat, shirin (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Improving quality of life in a chronic disease such as hemophilia is a major goal of treatment. Hemophilic patients can be treated either prophylactically or on demand. Since haemophilia quality of life may be affected by the disease and treatment outcomes, comparison of these regimens in respect to quality of life outcomes provides useful information. The purpose of this study is to compare the quality of life between hemophilic children receiving prophylactic and on demand therapy in Tehran, Iran. Materials and method: A descriptive –comparative design was used. The sample of the study consisted of 60 hemophilic children which were recruited from haemophilia treatment centres in Tehran. Of these children 30 were receiving prophylactic therapy and 30 of them were treated on- demand .Data was collected by haemophilia-specific QoL questionnaire (HAEMO-QoL). The questionnaire consists of 8 dimensions: physical health, feeling, view of yourself, family, friends, others, sport and dealing with haemophilia.The questionnaire consists of 18 items using a5-point scale.The Higher scores represent a poorer quality of life and lower scores represent better quality of life. Data were analyzed by SPSS 15 statistical software. Findings: The mean age of children was 5.3±1.2 and 6±1 in prophylactic and on demand therapy respectively. The mean total score of quality of life was 40±9.8 and 58 ±10.9 for children in prophylactic therapy and on-demand treatment respectively. There was a significant difference between the quality of life scores in two groups. Analysis of subscale scores showed a lower quality of life score for family domain in prophylactic therapy group, while the scores for family and physical health subscsles in on-demand group showed a poor quality of life. Conclusion: Results of the study suggest that quality-of-life may be better for haemophilia children